2017
DOI: 10.1016/j.cell.2017.01.024
|View full text |Cite
|
Sign up to set email alerts
|

The Ancient Gamete Fusogen HAP2 Is a Eukaryotic Class II Fusion Protein

Abstract: SummarySexual reproduction is almost universal in eukaryotic life and involves the fusion of male and female haploid gametes into a diploid cell. The sperm-restricted single-pass transmembrane protein HAP2-GCS1 has been postulated to function in membrane merger. Its presence in the major eukaryotic taxa—animals, plants, and protists (including important human pathogens like Plasmodium)—suggests that many eukaryotic organisms share a common gamete fusion mechanism. Here, we report combined bioinformatic, bioche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
227
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(256 citation statements)
references
References 69 publications
(92 reference statements)
13
227
1
Order By: Relevance
“…6) in spite of having a different fusogenic mechanism (Perez-Vargas et al, 2014). The very recent structural characterization of HAP2, a cellular protein required for fusion of gametes during fertilization, and which is conserved across the main branches of eukaryotic organisms (Wong and Johnson, 2010), again showed an unmistakable class II fusion fold (Fedry et al, 2017), although more distant to all of those observed up to now (which are represented in Figs. 3 and 6).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…6) in spite of having a different fusogenic mechanism (Perez-Vargas et al, 2014). The very recent structural characterization of HAP2, a cellular protein required for fusion of gametes during fertilization, and which is conserved across the main branches of eukaryotic organisms (Wong and Johnson, 2010), again showed an unmistakable class II fusion fold (Fedry et al, 2017), although more distant to all of those observed up to now (which are represented in Figs. 3 and 6).…”
Section: Discussionmentioning
confidence: 90%
“…The other members of this group have been included because of sequence similarity considerations. The eukaryotic gamete fusion protein HAP2, the X-ray structure of which was recently determined (Fedry et al, 2017), appears to have a more distant class II fold and was tentatively assigned to a separate lineage.…”
Section: Discussionmentioning
confidence: 98%
“…Several gene duplication events in the transition from archaea to eukarya explain the extensive paralogy observed in the trees. Fusogen HAP2 has neither traceable paralogues in eukaryotes nor homologs in archaea and was proposed to bear structural homology to viral proteins …”
Section: Proteins Associated With Sexual Processes Are Widespread In mentioning
confidence: 99%
“…Finally, structural and functional homologs of the class II fusion proteins have been found in eukaryotic organisms. The somatic cell-cell fusion protein EFF-1 from C. elegans (Pé rez-Vargas et al, 2014) makes syncytia necessary for skin formation during embryogenesis, and glycoprotein HAP2 is responsible for gamete fusion (or sperm/egg fusion) found in almost all the main branches of eukaryotes (Fedry et al, 2017). Organization of the Class II Genes Viral class II proteins are expressed within a polyprotein precursor, which contains at least two proteins (hantaviruses), and often more as in the case of the flaviviruses where all 10 virus-encoded proteins are derived from a single precursor polyprotein.…”
Section: The Class II Virusesmentioning
confidence: 99%